2005
DOI: 10.1104/pp.104.051169
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Two Closely Related Unicellular Thermo-Acidophilic Red Algae, Galdieria sulphuraria and Cyanidioschyzon merolae, Reveals the Molecular Basis of the Metabolic Flexibility of Galdieria  sulphuraria and Significant Differences in Carbohydrate Metabolism of Both Algae

Abstract: Unicellular algae serve as models for the study and discovery of metabolic pathways, for the functional dissection of cell biological processes such as organellar division and cell motility, and for the identification of novel genes and gene functions. The recent completion of several algal genome sequences and expressed sequence tag collections and the establishment of nuclear and organellar transformation methods has opened the way for functional genomics approaches using algal model systems. The thermo-acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
137
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(140 citation statements)
references
References 114 publications
3
137
0
Order By: Relevance
“…Genomic analyses of carbon metabolism have suggested that Cyanidioschyzon merolae, as G. sulphuraria, harbors metabolic pathways for floridoside, trehalose, storage glucans, and matrix polysaccharides [16]. C. merolae is predicted to contain a minimal set of metabolic transporters but no aquaporin-type glycerol permease for uptake of glycerol from the environment, or plastidic dicarboxylate translocators, which are required for nitrogen assimilation and for photorespiration and which are conserved in green plants and algae [17].…”
Section: Resultsmentioning
confidence: 99%
“…Genomic analyses of carbon metabolism have suggested that Cyanidioschyzon merolae, as G. sulphuraria, harbors metabolic pathways for floridoside, trehalose, storage glucans, and matrix polysaccharides [16]. C. merolae is predicted to contain a minimal set of metabolic transporters but no aquaporin-type glycerol permease for uptake of glycerol from the environment, or plastidic dicarboxylate translocators, which are required for nitrogen assimilation and for photorespiration and which are conserved in green plants and algae [17].…”
Section: Resultsmentioning
confidence: 99%
“…However, recent investigations strongly suggest that at least Rhodophyceae (Barbier et al 2005;Coppin et al 2005) and possibly also Glaucophyta (Plancke et al 2008) synthesize their starch from a far simpler set of analogous enzymes. These consist of soluble and granule-bound starch synthases, branching enzyme, transglucosidase, D enzyme, debranching enzyme, GWD, laforin, phosphorylase, and b-amylase but in fewer isoforms (for a detailed analysis see Deschamps et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the identification and characterization of genes encoding putative IP 3 or IP 6 receptors of unknown structure is of the highest priority for elucidating and comparing the regulation of the PI-PLC signalling cascade between IP 3 receptor-carrying and -lacking algae. Ostreococcus lucimarinus [9] Chlorophyceae Volvocales Chlamydomonadaceae Chlamydomonas reinhardtii [10] Volvocaceae Volvox carteri [11] Chlorococcales Coccomyxaceae Coccomyxa subellipsoidea [12] Rhodophyta Cyanidiophyceae Cyanidiales Cyanidiaceae Cyanidioschyzon merolae [13] Galdieria sulphuraria [14] Porphyridiophyceae Porphyridiales Porphyridiaceae Porphyridium purpureum [15] Rhodophyceae Bangiales Bangiaceae Pyropia yezoensis [16] Florideophyceae Gigartinales Gigartinaceae Chondrus crispus [17] Glaucophyta Glaucophyceae Glaucocystales Glaucocystaceae Cyanophora paradoxa [18] Heterokontophyta Coscinodiscophyceae Thalassiosirales Thalassiosiraceae Thalassiosira pseudonana [19] Bacillariophyceae Naviculales Phaeodactylaceae Phaeodactylum tricornutum [20] Pelagophyceae …”
mentioning
confidence: 99%
“…However, although the PI-PLC signaling cascade is present in plants [5][6][7], genes encoding PKC and the IP 3 receptor have not been found in terrestrial plant genomes, suggesting differences in second messenger systems between animals and plants. To date, the genomes of a variety of unicellular and multicellular algae have been sequenced [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] as shown in (Table 1). In addition, large-scale EST information for the red seaweeds Porphyra umbilicalis and Porphyra purpurea has been accumulated [24][25][26].…”
mentioning
confidence: 99%